Asset purchases as a remedy for the original sin redux - Yasin Mimir; Enes Sunel (Norges Bank, 2021)
We provide a theory on how a wider foreign lending base of local-currency sovereign debt may lead to destabilising effects (the original sin redux). Bond sell-offs by foreigners induce domestic banks to fund the government, reducing the credit for investment and tightening financial conditions. Currency mismatches exacerbate the ensuing deterioration in financial sector balance sheets, which amplifies the repercussions of the initial shock by prompting private sector capital outflows and larger currency depreciations. We then explore the role of central bank government bond and firm security purchases in countervailing the ramifications of bond sell-offs. Our estimated model reflects the regularities of the representative emerging-market economy that deployed quantitative easing policies during the pandemic. It further offers an explanation to the puzzle of stable exchange-rate dynamics accompanied by a reduction in excess sovereign bond yields and larger room for conventional monetary policy easing. We conclude asset purchases should be large in size to have a persistent effect on financial conditions and are less effective when they de-anchor inflation expectations or pose risks to a consolidated government balance sheet.
hdl:11250/2783873
Keywords: E62; E63; G21; 330; Asset purchases; original sin redux; Bayesian estimation